Factors Affecting Enrolment in the Community Based Health Insurance Scheme of Chandranigahapur Hospital of Rautahat District - Adhikari, Nilaramba; Wagle, Rajendra Raj; Adhikari, Dilli Raman; Thapa, Puspa; Adhikari, Muna (Journal of Nepal Health Research Council, 2019)
Background: Low income countries face considerable challenges in financing health care for their populations. As its consequences, poor people don’t have access to desired health services, drugs and medicine.To address the financial barriers to health services, Government of Nepal introduced Community Based Health Insurance scheme at selected health facilities. However, enrolment in the schemeis very low. This study aims to identify the associated factors affecting enrolment in the insurance scheme.Methods: A community based case-control study was conducted within the coverage area of CBHI scheme of Chandranigahapur Hospital. CBHI Scheme of Chandranigahapur Hospital was selected purposively. Altogether 416 households were interviewed using a structured questionnaire. The required number of sample size from the enrolled households as cases and equal number of non-enrolled households as controls were selected randomly in 1:1 ratio.Results: The odds of enrolment in the CBHI scheme among male-headed households were found lower than female-headed households (AOR 0.251, 95% CI 0.097 to 0.652). Similarly household head belonging to upper caste/ethnic groups (AOR 3.981, 95% CI 2.027 to 7.816) as well aseducated household head(AOR 6.184, 95% CI 3.137 to 12.188)were more likely to enrol in the CBHI scheme. Households having >60 years elderly were found significantly associated with enrolment in CBHI scheme(AOR 3.996, 95% CI 2.130 to 7.497). Time to reach health facility as well as affordability of premium of the insurance scheme was also found significantly associated with enrolment in the CBHI scheme.Conclusions: The enrolment in the CBHI scheme is determined by combination of householdhead, household and health service related factors.These determinants should be addressed to enhance the enrolment in the insurance scheme.Keywords: Community based health insurance; enrolment; health insurance; social health security.